Selection of parents for low nitrogen stress through the combining ability of maize partially inbred lines (Acta Scientiarum. Agronomy, 2019)
The objective of this work was to estimate the general combining ability of partially inbred lines under high and low nitrogen (N) conditions and to select promising lines to obtain high yields for both conditions. Fifty-five partially inbred S1 progenies were evaluated using the top-cross method, where the lines were crossed with two testers. The 110 top-cross hybrids were evaluated for grain yield during the off-season of 2012 at two sites in the Brazilian Midwest. Partial diallel analysis was performed with the adjusted means of each of the individual analyses of the top crosses. The combining ability of partially inbred lines and testers as well as their interaction with N levels, was estimated for each site. The coefficient of concordance among 15 partially inbred lines selected by the highest general combining ability estimates for each N level was 0.60. The S1 lines 39, 11, 41, 55, 38, 37, 6, 8, and 14 were selected at both N levels. This indicates that these lines can be used to identify ideal hybrids for growing in the off-season in the Brazilian Midwest.